Influence of Sociodemographic Factors and Knowledge in Pedagogy on the Labor Market Insertion of Education Science Professionals - María Pilar Cáceres-Reche; Susana Tallón-Rosales; Magdalena Ramos Navas-Parejo; Juan Carlos De la Cruz-Campos (Education Sciences, 2022)
The profile of the pedagogy student is polyvalent, the motivations, competencies, attitudes, and necessary aptitudes are also varied and suitable for developing the exercise of their profession in different labor scenarios, ranging from the educational-training context to the business context. The aim of this research has been to analyze the influence of sociodemographic factors and knowledge in pedagogy on labor market insertion, expectations about the degree, and employability of students of the degree in pedagogy at the University of Granada, Spain. The methodology used was based on a cross-sectional study design through a survey administered to a total of 334 students. The results obtained show that there are differences between the two genders. Regarding the year of study, no significant differences were found. Knowledge about the profile of the pedagogue is a factor that does influence expectations about the degree, job placement, and employability. However, expectations about the degree did not influence job placement, although employability did. It is concluded by stating that there is a lack of knowledge about the role of the pedagogue, which needs to be alleviated, as well as highlighting the need to reinforce the curricular, academic, and practical training of this degree.